Application of DCA to study distributive patterns of Isodon in China - GUO Shui-liang; CAO Tong (浙江大学学报. 农业与生命科学版)
The distributive patterns of Chinese Isodon were studied by Detrended Correspondence analysis (DCA). The results are as follows: ①The geographic distribution of Chinese Isodon could be divided into four regions including Southwestern China area, Southern China area, Eastern-Central China area and Northern China area; ②The area including Northwestern Yunnan, West Sichuan and Southeastern Xizhang is the diversity center of the Chinese Isodon; ③The geographic elements of Chinese Isodon include the element endemic to China, Eastern Asian element and Tropical Asian element, accounting for 78.2%, 18.4% and 3.4% of the total species of the genera in China respectively; ④DCA is more applicable than PCA (Principal Component Analysis) in florology and phytogeography.